Optical tomography system: Application of Charge Coupled Device (CCD) for solid and transparent objects detection - Juliza Jamaludin; Abdul Rahim R.; Abdul Rahim H.; Fazalul Rahiman H.; Mohd Muji S.Z.; Jumaah M.F.; Mohd Fadzil N.S. (Penerbit UTM Press, 2024)
Indexed by WOS/ Scopus